Surgical Implant Generation Network (SIGN) Fin nail versus SIGN standard intramedullary nail for distal diaphyseal femur fractures treated via retrograde approach. Issue 10 (October 2019) - Liu, Max Bolun; Ali, Syed Haider; Haonga, Billy Thomson; Eliezer, Edmund Ndalama; Albright, Patrick David; Morshed, Saam; Shearer, David
Highlights: SIGN Standard Nail and SIGN Fin Nail are intramedullary nails developed for settings without fluoroscopy. Fin Nail provided comparable outcomes (reoperation rate, infection, non-union, EQ5D, RUST score, Squat & Smile) to Standard Nail at 1 year. Fin Nail was associated with greater patient pain in early post-operative period, but this difference resolved over time. Fin Nail may be a useful alternative to locked Standard IM Nails for fixation of distal diaphyseal femur fractures without fluoroscopy. Abstract: Introduction: Surgical fixation of distal diaphyseal femur fractures remains a major challenge in developing countries given limited availability of fluoroscopy. The Surgical Implant Generation Network (SIGN) Standard Intramedullary Nail and SIGN Fin Nail are two modalities developed to address this challenge; the Fin Nail additionally avoids needing to place proximal interlocking screws. While efficacy of the Standard Nail has been established, outcomes following fixation with the Fin Nail are unknown. In this study, we compare outcomes of distal diaphyseal femur fractures treated with each implant. Methods: A prospective cohort study was conducted from 2012 to 2013 at a single tertiary-referral center in Tanzania. Skeletally mature patients with distal diaphyseal femur fractures treated with either retrograde SIGN Standard Nail or Fin Nail were included. Patients followed-up at 6, 12, 26, and 52 weeks post-operatively. The primary outcome was all-cause reoperation. Secondary outcomes included infection, non-union, malalignment, quality of life (EQ-5D score), pain (VAS score), radiographic healing (RUST score), and function (pain with weight bearing, knee range of motion, and Squat and Smile score). Results: 74 (85%) of 85 enrolled patients completed the minimum 1-year follow-up. There was no difference in rate of reoperation (p = 1.00), infection (p = 1.00), limb length discrepancy (p = 0.47), non-union (p = 1.00), or coronal or sagittal malalignment (p = 1.00, p = 0.55 respectively) at 1 year. There was furthermore no difference in mean EQ-5D (p = 0.82), VAS pain score (p = 0.43), RUST score (p = 0.44), maximum knee flexion (p = 0.52) and extension (p = 1.00), or Squat and Smile function (p = 1.00) between cohorts at 1 year. Discussion: Outcomes associated with the SIGN Fin Nail are comparable to those associated with the SIGN Standard Intramedullary Nail at 1 year. The SIGN Fin Nail may be useful as an alternative to Standard locked IM nails for fixation of distal diaphyseal femur fractures.